2019
DOI: 10.1111/liv.14066
|View full text |Cite
|
Sign up to set email alerts
|

TCRβ repertoire of memory T cell reveals potential role for Escherichia coli in the pathogenesis of primary biliary cholangitis

Abstract: Background Primary biliary cholangitis (PBC) is an organ‐specific, T cell‐mediated autoimmune disease which is characterized by the breakdown of self‐tolerance to the highly conserved pyruvate dehydrogenase complex, especially the pyruvate dehydrogenase E2 complex (PDC‐E2). However, the molecular mechanism of breakdown of self‐tolerance is still unclear. Methods A combination of multiplex‐PCR and immune repertoire sequencing (IR‐seq) was used for a standardized analysis of memory T cell receptor (TCR) β‐chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In the early stage of PBC, NK cell killing activity is enhanced, and monocytes and macrophages have a high response to pathogen-associated antigens (66). Then, Th1 cells and cytotoxic T lymphocyte are activated (67,68). Furthermore, autoreactive B cells secrete large amount of antimitochondrial antibodies (69).…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%
“…In the early stage of PBC, NK cell killing activity is enhanced, and monocytes and macrophages have a high response to pathogen-associated antigens (66). Then, Th1 cells and cytotoxic T lymphocyte are activated (67,68). Furthermore, autoreactive B cells secrete large amount of antimitochondrial antibodies (69).…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%
“…We selected the top 20 items of GO with the lowest p value to show in the Figure 2A. Among them, some GO terms were previously studied to be associated with the pathogenesis of HCC and liver disease, such as cytokine activity (Diao et al , 2012), RNA polymerase II transcription factor binding (Stefanska et al , 2013), signal transducer, downstream of receptor, with serine/threonine kinase activity (Hou et al , 2019), and mitogen-activated protein kinase binding (Yang et al , 2014). These results were consistent with the finding that complicated connections exist within the mechanism of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + naive and CD4 + memory cells were defined as CD4 + CD8 − CD45RA + CD45RO − and CD4 + CD8 − CD45RA − CD45RO + , respectively. CD8 + naive and CD8 + memory cells were defined as CD4 − CD8 + CD45RA + CD45RA − and CD4 − CD8 + CD45RA − CD45RO + , respectively 9 . The number of each T‐cell subset isolated from each donor is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…CD8 + naive and CD8 + memory cells were defined as CD4 À CD8 + CD45RA + CD45RA À and CD4 À CD8 + CD45RA À CD45RO + , respectively. 9 The number of each T-cell subset isolated from each donor is shown in Table S1. Flow cytometry (FACS) analysis confirmed that all sorted populations contained more than 500 000 cells and > 95% pure.…”
Section: Subjectsmentioning
confidence: 99%